2016
DOI: 10.1080/09658211.2016.1150490
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural differences in children's earliest memories

Abstract: The purpose of the present study was to address the effects of urban vs. rural upbringing on earliest autobiographical memories. We asked children (aged 10-13) brought up in an urban vs. in a rural setting to report their earliest memories. Earliest memories of children from rural areas were a year later than those of children from urban areas. Moreover, memories of children from rural areas were more likely to contain social interactions and tended to be less detailed compared to those from urban areas. The g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…The age from which young and middle-aged adults remembered their earliest childhood memories is in line with previous research showing that infantile amnesia wanes between age three and four (e.g., Davis et al, 2008;Eacott, 1999). The age at the time of the earliest memories obtained in the present research is also similar to those observed in other studies conducted with Turkish samples (e.g., Demircan 2012;Ece, Demiray, & Gülgöz, 2019;Göz, Çeven, & Tekcan, 2017;Yıldırım, Soncu-Büyükişcan, Çolak, Akpınar, & Altan, 2018). In general, current findings were in line with the hypotheses: (1a) Earliest memories were rated lower in all memory characteristics than later memories, (1b) free-report memories were higher in importance, emotionality and rehearsal frequency, but lower in vividness and confidence in the reality of memory than recent memories, (2) middle-aged adults generally rated Psikoloji Çalışmaları -Studies in Psychology Cilt/Volume: 39, Sayı/Issue: 1, 2019 both earliest and later memories higher on memory characteristics than young adults, and (3a) the age of earliest and (3b) free-report memories differed as a function of retrieval order.…”
Section: Discussionsupporting
confidence: 92%
“…The age from which young and middle-aged adults remembered their earliest childhood memories is in line with previous research showing that infantile amnesia wanes between age three and four (e.g., Davis et al, 2008;Eacott, 1999). The age at the time of the earliest memories obtained in the present research is also similar to those observed in other studies conducted with Turkish samples (e.g., Demircan 2012;Ece, Demiray, & Gülgöz, 2019;Göz, Çeven, & Tekcan, 2017;Yıldırım, Soncu-Büyükişcan, Çolak, Akpınar, & Altan, 2018). In general, current findings were in line with the hypotheses: (1a) Earliest memories were rated lower in all memory characteristics than later memories, (1b) free-report memories were higher in importance, emotionality and rehearsal frequency, but lower in vividness and confidence in the reality of memory than recent memories, (2) middle-aged adults generally rated Psikoloji Çalışmaları -Studies in Psychology Cilt/Volume: 39, Sayı/Issue: 1, 2019 both earliest and later memories higher on memory characteristics than young adults, and (3a) the age of earliest and (3b) free-report memories differed as a function of retrieval order.…”
Section: Discussionsupporting
confidence: 92%
“…In the results described in Chapter 2, mock witnesses from the urban collectivistic cultural group reported more details than those from the rural collectivistic cultural group. A similar pattern has been reported in research on autobiographical memory reports, where children from rural collectivistic cultures report fewer details than children from urban collectivistic cultures (Göz, Çeven, & Tekcan, 2017). With the exception of the experiment reported in Chapter 2, all the collectivistic samples in this programme of research were urban collectivistic samples.…”
Section: Scope and Generalisability Of The Current Programme Of Researchsupporting
confidence: 82%
“…Similarly, the tendency for misinformation acceptance may be higher for rural collectivistic samples than an urban collectivistic sample. This is because previous work shows within collectivistic cultures, rural areas tend to be more collectivistic than urban areas (Göz, Çeven, & Tekcan, 2017;Ma et al, 2015), where hierarchy is emphasised and the interdependent self is predominant (Babes & Ros, 2005;Markus & Kitayama, 1991;Minkov et al, 2017). Consequently, hierarchy and reliance on social sources of information may be more pronounced in rural collectivistic cultures than urban collectivistic cultures.…”
Section: Scope and Generalisability Of The Current Programme Of Researchmentioning
confidence: 93%
“…They tell less detailed personal narratives and focus more on group norms and group needs and less on their own activities, thoughts, and feelings (Pillemer, 1998; Leichtman et al, 2003). Easterners also describe themselves more in terms of relationships than of personal attributes (Wang, 2006, 2016; Göz et al, 2017). As expected by Kağıtçıbaşı (2005), these differences do not only show between Western and Eastern countries, but also within countries, for instance between Western and Eastern Turkey (Sahin-Acar and Leichtman, 2015).…”
Section: Introductionmentioning
confidence: 99%